Elevated levels of interleukin‐33 are associated with allergic and eosinophilic asthma. (18th March 2019) - Gasiuniene, Edita; Janulaityte, Ieva; Zemeckiene, Zivile; Barkauskiene, Diana; Sitkauskiene, Brigita
Abstract: IL‐33 is a recently discovered cytokine which plays an important role in asthma pathogenesis. Aim: To evaluate serum IL‐33 in patients with asthma and healthy controls, and to evaluate the association of IL‐33 with different asthma phenotypes. Methods: Patients with asthma (n = 115) and healthy subjects (n = 85) were included in the study. Subjects with asthma were divided into groups according to their phenotype: allergic/non‐allergic, eosinophilic/non‐eosinophilic, obese/non‐obese and severity according to GINA (mild, moderate and severe). The concentration of IL‐33 in serum was measured by standardized enzyme‐linked immunosorbent assay. Results: The level of IL‐33 was significantly higher in patients with asthma when compared to healthy subjects (672.73 ± 104.47 pg/mL vs 268.52 ± 27.56 pg/mL, P  < 0.05). IL‐33 was also higher in the allergic asthma group patients when compared to non‐allergic asthmatics (844.61 ± 152.08 pg/mL vs 369.56 ± 77.94 pg/mL, P  < 0.05). There was a significantly higher serum IL‐33 level in the eosinophilic asthma group when compared to the group of non‐eosinophilic asthma patients (1001.10 ± 199.11 pg/mL vs 337.49 ± 72.68 pg/mL, P  < 0.01). We did not find a significant difference in serum IL‐33 level between different asthma severity groups, obese and non‐obese asthmatics. Conclusion: IL‐33 is increased in asthma patients, particularly in some phenotypes: allergic asthma and eosinophilic asthma.